Chest compression with 2-DOF parallel manipulator for cardiopulmonary resuscitation - Yedukondalu, G; Patnaik, Sajjan; Lakshmi Venkatesh, P; Siva Jagadeesh, S (International Journal of Engineering and Technology, 2018)
Chest compression process is used for recovering patients who met with a cardiac arrest in emergency situations. Chest compression is the only possibility of rescuing patients during cardiopulmonary resuscitation (CPR). It is hard to achieve the exact chest compression’s depth and rate even by experienced professionals as per the CPR guideline. A 2-DOF 2-RRR translational parallel manipulator was designed for delivering chest compressions. The kinematic analysis is carried out analytically. The workspace of the manipulator is examined in consideration of physical constraints imposed by joints. Finally, the manipulator operates with exact compression depth and rate during CPR.
Keywords: Parallel Manipulator; chest compression; Cardiopulmonary Resuscitation(CPR).